Common fixed points of an infinite family of nonexpansive mappings in uniformly convex metric spaces - Phuengrattana W. (2014)
We generalize the notion of K-mapping due to Kangtunyakarn and Suantai (2009). [1] for an infinite family of nonexpansive mappings on a convex metric space and study some of its useful properties. We also establish strong convergence of a Mann type iterative sequence to a common fixed point of an infinite family of nonexpansive mappings on a uniformly convex metric space. © 2012 Elsevier Ltd.